Performance of Sparse Code Multiple Access Communication System Based on Logarithmic Message Passing Algorithm and Low-Density Parity Check Code - Moafaq, Mustafa; Al-Azawi, Maher (Iraqi Journal for Electrical and Electronic Engineering, 2025)
The performance of Sparse Code Multiple Access (SCMA) communication system with Logarithmic Message Passing Algorithm (log-MPA) decoder is introduced. To boost the performance, a Low-Density Parity-Check Code LDPC is used together with Belief Propagation (BP) decoder. LDPC is chosen due to its sparsity property that complements the sparsity nature of SCMA for maximum efficiency and minimum complexity. Three distinct SCMA configurations are used. These are: A (4 x 4 x 6), B (4 x 16 x 6), and C (5 x 4 x 10) where the (K x M x V) are numbers of resources, codewords and users respectively. The performance of these configuration is shown in various channel conditions, various LDPC code rates and various numbers of SCMA iterations (NSCMA), to find the local minimum value of log-MPA. Simulation results showed that the LDPC greatly boosted the performance in mentioned configurations: In A configuration, a gain of 13 dB was observed. Configuration B experienced a substantial improvement of 23.5 dB, while C achieved a gain of 20.5 dB. Notably, configuration B stood out with the highest gain, attributed to LDPC’s exceptional performance with high data rates, as the data transmitted in B was double that of A.